Permeability, compressive strength and Proctor parameters of silts stabilised by Portland cement and ground granulated blast furnace slag (GGBFS) - Per Lindh; Polina Lemenkova (Archive of Mechanical Engineering, 2022)
The study investigates the effect of Portland cement and ground granulated blast furnace slag (GGBFS) added in changed proportions as stabilising agents on soil parameters: uniaxial compressive strength (UCS), Proctor compactness and permeability. The material included dredged clayey silts collected from the coasts of Timrå, Östrand. Soil samples were treated by different ratio of the stabilising agents and water and tested for properties. Study aimed at estimating variations of permeability, UCS and compaction of soil by changed ratio of binders. Permeability tests were performed on soil with varied stabilising agents in ratio H WL B (high water / low binder) with ratio 70/30%, 50/50%, and 30/70%. The highest level of permeability was achieved by ratio 70/30% of cement/slag, while the lowest - by 30/70%. Proctor compaction was assessed on a mixture of ash and green liquor sludge, to determine optimal moisture content for the most dense soil. The maximal dry density at 1.12 g/cm 3 was obtained by 38.75% of water in a binder. Shear strength and P-wave velocity were measured using ISO/TS17892-7 and visualised as a function of UCS. The results showed varying permeability and UCS of soil stabilised by changed ratio of CEM II/GGBS.